Analisis Persepsi Mahasiswa Terhadap Metode Pengajaran Kreasi Bisnis - Muliadi Palesangi; Sri Widya Wijanarti; Sonny Agustiawan (Universitas Islam Nahdlatul Ulama Jepara, 2020)
In the world of entrepreneurship education, it is important for educators to find the combination of entrepreneurial teaching methods that relevant to the learning goals and students’ needs. This quantitative research aims to get an overview from students' perceptions of Business Creation’s teaching methods in Prasetiya Mulya University, S1 Business Program. The results of the study revealed that discussion about STDP, Marketing Mix and BMC perceived as three important topics in starting a business in the aspect of conceptual lecture. The first and final phases of the competition are perceived to have a positive impact to fostering an entrepreneurial spirit in aspects of competition simulation. Whereas in the aspect of group dynamics, the factors that greatly influence group performance are communication and collaboration. The most interesting discussion topics for students are Opportunity, BMC, and Operation Skill.